The Influence of Business Capital, Financial Inclusion, and Intellectual Capital on MSME Performance (A Case Study of the Culinary Sector in Harjamukti District, Cirebon City) - Febiyanti Febiyanti; Rinni Indriyani; Muzayanah Muzayanah (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2026)
Improving the performance of MSMEs is crucial for supporting economic growth and community welfare. This study aims to analyze the impact of business capital, financial inclusion, and intellectual capital on the performance of MSMEs in the culinary sector of Harjamukti District, Cirebon City. The study employs a quantitative approach using multiple linear regression analysis. The research population consists of 986 MSMEs, with a sample of 91 MSMEs determined using the Slovin formula. Data were collected via Likert-scale questionnaires. The results indicate that business capital and financial inclusion have a positive and significant effect on MSME performance, whereas intellectual capital does not have a significant effect. However, simultaneously, the three variables significantly influence MSME performance. These findings highlight the importance of strengthening business capital and financial inclusion to enhance MSME performance.